Cost-utility of medication withdrawal in older fallers: results from the improving medication prescribing to reduce risk of FALLs (IMPROveFALL) trial. Issue 1 (December 2016) - Polinder, Suzanne; Boyé, Nicole; Mattace-Raso, Francesco; Van der Velde, Nathalie; Hartholt, Klaas; De Vries, Oscar; Lips, Paul; Van der Cammen, Tischa; Patka, Peter; Van Beeck, Ed; Van Lieshout, Esther
Abstract Background The use of Fall-Risk-Increasing-Drugs (FRIDs) has been associated with increased risk of falls and associated injuries. This study investigates the effect of withdrawal of FRIDs versus 'care as usual' on health-related quality of life (HRQoL), costs, and cost-utility in community-dwelling older fallers. Methods In a prospective multicenter randomized controlled trial FRIDs assessment combined with FRIDs-withdrawal or modification was compared with 'care as usual' in older persons, who visited the emergency department after experiencing a fall. For the calculation of costs the direct medical costs (intramural and extramural) and indirect costs (travel costs) were collected for a 12 month period. HRQoL was measured at baseline and at 12 months follow-up using the EuroQol-5D and Short Form-12 version 2. The change in EuroQol-5D and Short Form-12 scores over 12 months follow-up within the control and intervention groups was compared using the Wilcoxon Signed Rank test for continuous variables and the McNemar test for dichotomous variables. The change in scores between the control and intervention groups were compared using a two-way analysis of variance. Results We included 612 older persons who visited an emergency department because of a fall. The mean cost of the FRIDs intervention was €120 per patient. The total fall-related healthcare costs (without the intervention costs) did not differ significantly between the intervention group and the control group (€2204 versus €2285). However, the withdrawal of FRIDs reduced medication costs with a mean of €38 per participant. Furthermore, the control group had a greater decline in EuroQol-5D utility score during the 12-months follow-up than the intervention group (p  = 0.02). The change in the Short Form-12 Physical Component Summary and Mental Component Summary scores did not differ significantly between the two groups. Conclusions Withdrawal of FRID's in older persons who visited an emergency department due to a fall, did not lead to reduction of total health-care costs. However, the withdrawal of FRIDs reduced medication costs with a mean of €38 per participant in combination with less decline in HRQoL is an important result. Trial registration The trial is registered in the Netherlands Trial Register (NTR1593 – October 1st 2008).